Comparison of Gamma Index Passing Rate in Several Treatment Planning System Algorithms - S. Liura; S.A. Pawiro (Atom Indonesia, 2020)
The verification of dose calculation algorithm in a new Treatment Planning System (TPS) can be evaluated by comparing the passing rate of the gamma index analysis of the evaluated algorithm and the clinically implemented algorithms. In the present investigation, the gamma index passing rates was investigated as the reference data in the verification of the new three-dimensional TPS. The algorithms which are used in this study are Pencil Beam Convolution (PBC) version 11.0.31 and Anisotropic Analytical Algorithm (AAA) version 11.0.31 in Eclipse v.11 TPS, and Fast Convolution (FC), Adaptive Convolution (AC), and Collapsed-Cone Convolution (CCC) in Pinnacle3 v.7.6c TPS. The 6 MV X-ray beam configurations were varied in the depth of measurement points, field sizes, source-to-surface distances, and wedge angles. The dose measurement was done using MatriXX Evolution and PTW 2D-array seven29. Then, OmniPro ImRT and Verisoft 3.1 software were chosen to analyze the gamma index from varied gamma criteria (3 %/3mm, 2 %/3mm, 3 %/2mm, and 2 %/2mm). Overall, the passing rate of AAA is the highest rate obtained of all algorithms. For gamma criterion of 2 %/2mm, the passing rate of AAA was 93.18 % ± 7.21 %, the passing rate of PBC was 89.76 % ± 7.21 %, and the passing rate of convolution algorithms was 76.84 % ± 11.10 %.